A Facile and Green Protocol for Nucleophilic Substitution Reactions of Sulfonate Esters by Recyclable Ionic Liquids [bmim][X] - Liu, Yajun; Xu, Yongnan; Jung, Sun Ho; Chae, Junghyun (Synlett, 2012)
Ionic liquids [bmim][X] (X = Cl, Br, I, OAc, SCN) are highly efficient reagents for nucleophilic substitution reactions of sulfonate esters derived from primary and secondary alcohols. The counter anions (X–) of the ionic liquids, [bmim][X], effectively replace the sufonates affording the corresponding substitution products such as alkyl halides, acetates, and thiocyanides in excellent yields. The newly developed protocol is very environmentally attractive because the reactions use stoichiometric amounts of ionic liquids as sole reagents in most cases and do not require additional solvents, any other activating reagents, non-conventional equipment, or special precautions. Moreover, these ionic liquids can be readily recycled without loss of reactivity, making the whole process ‘greener’.
Keywords: ionic liquids; nucleophilic substitution; halogenation; recyclability; green chemistry